Knight and Moon: Curious Minds - Book 1 - Evanovich, Janet; Sutton, Phoef (New York : Bantam Books, 2016)
"Janet Evanovich, #1 New York Times bestselling author of the Stephanie Plum series, teams up with Emmy-winning writer Phoef Sutton for a brand-new series of thrillers featuring charmingly eccentric Emerson Knight and professional go-getter Riley Moon"--
"A brand-new series introducing a fun and entertaining crime-solving team with great romantic chemistry--fiesty financial analyst Riley Moon and eccentric savant Emerson Knight. Riley Moon is a junior analyst at a mega-bank, when she uncovers what looks like an embezzlement scheme that could lead straight to the top. With his gold gone missing and analysts disappearing, famously eccentric Emerson Knight, the bank's biggest client, decides to take on his own investigation. With Emerson's laserlike focus and ability to see clues no one else sees, and Riley's financial-whiz mind and street savvy, this unlikely pair will uncover one of the biggest crimes of the century"--
Publishers Weekly
Kirkus Reviews
Adult.
Adult.
Keywords: Humorous fiction; Love stories -- Fiction; Adventure fiction